The Paradox of Integrity: Cheating Awareness Among Religious High School Student in Yogyakarta [Paradoks Integritas: Kesadaran akan Perilaku Kecurangan di Kalangan Siswa Sekolah Menengah Atas Berbasis Agama di Yogyakarta] - Samudera Fadlilla Jamaluddin; Galang Lufityanto (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
Cheating behavior in a school setting has become a major problem in many countries, including those with a dominantly religious population (e.g., Indonesia). This creates a paradox since previous literatures suggest eminent role of spirituality in constructing morality. This study is intended to investigate the interplay between spirituality and cheating behavior in religious high school students in Yogyakarta using multi-methods approach. Self-report questionnaires to measure the perception toward cheating, spirituality level, and locus of control were distributed to a total of 691 participants using random sampling method. Participants were also given an open-ended questionnaire asking the rationale behind their past cheating behavior. The findings suggested that the role of spirituality in ethical behavior was rather contextual, such as the link between spirituality and awareness of cheating was more robust in the respondents from religious schools. It was found that the participants viewed spirituality as an internal moral compass which may in turn facilitate overt ethical behavior. Perilaku kecurangan di sekolah telah menjadi permasalahan besar di berbagai negara, termasuk di negara-negara yang mayoritas penduduknya religius (misalnya di Indonesia). Hal ini menimbulkan sebuah paradoks mengingat penelitian terdahulu menyatakan bahwa spiritualitas berperan dalam proses pembentukan moralitas. Penelitian ini bertujuan untuk menelaah interaksi antara spiritualitas dan perilaku kecurangan pada siswa sekolah menengah di Yogyakarta menggunakan pendekatan multi-metode. Kuesioner laporan diri untuk mengukur persepsi terhadap kecurangan, tingkat spiritualitas, dan lokus kendali dibagikan kepada total 691 partisipan menggunakan metode random sampling. Partisipan juga diberikan kuesioner dengan butir-butir pertanyaan terbuka yang menanyakan alasan di balik perilaku curang mereka di masa lampau. Temuan menunjukkan bahwa peran spiritualitas dalam perilaku etis cenderung bersifat kontekstual, misalnya hubungan antara spiritualitas dan kesadaran akan perilaku kecurangan lebih kuat pada responden dari sekolah berbasis agama. Ditemukan bahwa partisipan dalam kajian ini memandang spiritualitas sebagai kompas moral internal yang dapat berperan dalam memfasilitasi perilaku etis yang terbuka.